Screening for Antibacterial Activity of Turnera subulata Extracts against Human Pathogens - Murugan, T (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe herbal plants are considered as hidden treasures and explored for novel drugs for more than a decade. Turnera subulata was one of the least explored medicinal plants which are assumed to have antimicrobial potential because they are used in Tamil medicinal (Siddha) preparations. Leaves extracts were obtained by hexane, petroleum ether, chloroform and acetone. Discs were prepared by impregnating 5%, 10% and 15% concentration of extract. The positive controls were Chloromphenical, Kanamycin and Erythromycin. The extracts were tested against Proteus vulgaris, Klebsiella pneumoniae, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. Proteus vulgaris showed sensitive to acetone extract, Staphylococcus aureus and Klebsiella pneumoniae to chloroform extract. Other two species showed resistant to all the extract tested.Key words: Turnera subulata, leave extract, human pathogens and positive control.